Metadata and Semantic Research: 13th International Conference, MTSR 2019, Rome, Italy, October 28-31, 2019, Revised Selected Papers - Garoufallou, Emmanouel; Fallucchi, Francesca; William De Luca, Ernesto (Communications in Computer and Information Science, 2019)
This book constitutes the thoroughly refereed proceedings of the 13th International Conference on Metadata and Semantic Research, MTSR 2019, held in Rome, Italy, in October 2019. The 27 full and 15 short papers presented were carefully reviewed and selected from 96 submissions. The papers are organized in the following tracks: metadata and semantics for digital libraries, information retrieval, big, linked, social and open data; metadata and semantics for agriculture, food, and environment; digital humanities and digital curation; cultural collections and applications; european and national projects; metadata, identifiers and semantics in decentralized applications, blockchains and P2P systems.